Pengaruh Pemberian Jus Selada Pada Pasien Terhadap Tingkat Kecemasan Pasien Pra Operasi Di Jogja Lasik Center Rs Mata "Dr. Yap" Yogyakarta - Nur Yeti Syarifah; Muryani; Mira Runy Cendrawasih (Journal of Health (JoH), 2021)
Background: Anxiety in pre-operative patients affects the success of lasik action and can cause problems such as psychosis and personality disorders. Non-pharmacological interventions that can overcome anxiety are juice drinks. Objective: Knowing the difference in the level of anxiety before and after drinking lettuce juice in patients with pre surgery at the Jogja Lasik Center Eye Hospital "Dr. YAP” Yogyakarta. Method: This type of research is a quasi-experimental with a pretest and posttest approach. The population in this study were all preoperative patients. The sampling technique used total sampling, the number of samples was 16 people, the data analysis used the independent t-test. Result: Results obtained an average difference in anxiety reduction after juice administration of 106.81. There was a difference in anxiety levels in pre-operative patients after being given Juice. Conclusion: Therapy is more effective compared to the juice against the anxiety level of pre-surgery patients at Jogja Lasik Center Rs Mata "Dr. YAP" Yogyakarta.